Implementation of The Merdeka Belajar Kampus Merdeka (MBKM) Curriculum in Addressing The Problems of Economic Education In The Era of Disruption and Society 5.0 at Jambi University - Noviatri Indah Puspita Sari; Rosmiati; Mayasari (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
Facing the era of disruption and Society 5.0, the field of education plays an important role in improving the quality of human resources. Therefore, the government has implemented the Merdeka Belajar Kampus Merdeka (MBKM) curriculum. This study aims to understand the implementation of the MBKM curriculum in addressing economic education issues in the era of disruption and Society 5.0, to examine its effectiveness, and to identify solutions to overcome obstacles in its implementation. This research employs a qualitative method with a descriptive design. Informants were selected using a purposive sampling technique, involving students as key informants and additional informants including the Head of the Economics Education Study Program, the Secretary of the Social Science Education Department, and several economics education lecturers at Jambi University, Indonesia. Data were collected through observation, interviews, and documentation, and analyzed using Nvivo 12 software. The results show that: (1) the implementation of the MBKM curriculum provides a positive direction for the development of students' skills through experiential learning; (2) the effectiveness of MBKM is reflected in students’ improved knowledge and skills, particularly in critical thinking, creativity, and collaboration; and (3) solutions for implementation require continuous curriculum adjustments and improvements. The implications of this study indicate that the MBKM curriculum can address the challenges of economic education in the era of disruption and Society 5.0 if implemented optimally and continuously evaluated. This study also suggests the need for strengthening curriculum design, institutional readiness, and collaboration with stakeholders to enhance the effectiveness of MBKM in higher education. Keywords: MBKM, economic education problems, disruption era, Society 5.0